THE PHENOMENON OF PICKING UP BALLS IN THE PPDB PROCESS (PHENOMENOLOGY STUDY OF PICKING UP FOOTBALL AT SMK SIANG 1 BOJONEGORO): FENOMENA PENJEMPUTAN BOLA DALAM PROSES PPDB (STUDI FENOMENOLOGI PENJEMPUTAN SEPAKBOLA SMK SIANG 1 BOJONEGORO) - Titin Sekartika (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Private educational institutions have various methods of recruiting students according to school needs. In general, these schools prefer to implement PPDB (New Student Admissions) with the